PUP-IT2 as an alternative strategy for PUP-IT proximity labeling - Yue, Suyu; Xu, Peng; Cao, Zhihe; Zhuang, Min (Frontiers in Molecular Biosciences, 2022)
PUP-IT is a proximity labeling method based on the prokaryotic enzyme PafA. PafA mediates the ligation of Pup, a small peptide, to the proximal proteins. It is different from other proximity labeling methods, such as BioID and APEX, in that both the enzyme and the labeling tag are proteins, which allows for potential in vivo applications. All proximity labeling involves the genetic fusion of the proximity labeling enzyme with the bait protein. However, PafA is a 55 kDa enzyme which sometimes interferes with the bait function. In this study, we tested an alternative proximity labeling strategy, PUP-IT2, in which only a small 7 kDa protein is fused to the bait protein. We examined the activity of PUP-IT2 in vitro and in cells. We also compared it with the original PUP-IT. Finally, we applied PUP-IT2 coupled mass spectrometry to map protein-protein interactions. Overall, we established a new way to use PUP-IT2 for proximity labeling, and this method may have a broad application.